Soil Infestation with Western Corn Rootworm Eggs and Larval Emergence Timing in the Right-Bank Forest-Steppe of Ukraine - Saliienko, V.; Remeniuk, S. (Quarantine and plant protection, 2024)
Goal. To determine the soil infestation with western corn rootworm (WCR) eggs depending on the duration of corn cultivation in one area, as well as to study the timing of larval development stages taking into account the sum of effective temperatures (SET) in the Right-Bank Forest-Steppe of Ukraine. Methods. The study was conducted in 2021—2023 in the fields of Khmilnyk district, Vinnytsia region. The methodology included soil sampling to analyze the number of eggs in samples measuring 10 × 10 cm and 15 cm deep. The samples were examined by washing and flotation using magnesium sulfate solutions, after which the number of eggs was determined under a microscope. Morphological assessment of the chorion surface was used to identify eggs. Additionally, phenological observations of the larval developmental stages based on the accumulation of SET were performed. Results. The number of eggs of the WCR varied from 11.3 to 47.6 per sample (1130—4760 pcs./m²). The lowest values were observed in the fields with two years of corn cultivation, and the maximum values were recorded in the fields with four years of crop cultivation. The dependence of the number of eggs on weather conditions was also significant: the driest year, 2022, was characterized by a reduced level of soil infestation compared to other years. The average time of hatching of the first instar larvae was recorded in the second decade of June at 150—160°C, the second instar — within 6—9 days after the emergence of the first instar larvae, and the third instar — in the third decade of June. Pupation occurred in late June — early July. Conclusions. The data obtained indicate that the intensity of soil infestation depends on the duration of corn cultivation in one field and weather conditions. The use of the SET method proved to be effective in predicting the stages of pest development. Results can be used to improve the monitoring system and optimize the timing of protective measures.